A sulphated glycosaminoglycan extract from Placopecten magellanicus inhibits the Alzheimer's disease β-site amyloid precursor protein cleaving enzyme 1 (BACE-1). (March 2023) - Mycroft-West, Courtney J.; Devlin, Anthony J.; Cooper, Lynsay C.; Guimond, Scott E.; Procter, Patricia; Miller, Gavin J.; Guerrini, Marco; Fernig, David G.; Yates, Edwin A.; Lima, Marcelo A.; Skidmore, Mark A.
Abstract: The clinically important anticoagulant heparin, a member of the glycosaminoglycan family of carbohydrates that is extracted predominantly from porcine and bovine tissue sources, has previously been shown to inhibit the β-site amyloid precursor protein cleaving enzyme 1 (BACE-1), a key drug target in Alzheimer's Disease. In addition, heparin has been shown to exert favourable bioactivities through a number of pathophysiological pathways involved in the disease processes of Alzheimer's Disease including inflammation, oxidative stress, tau phosphorylation and amyloid peptide generation. Despite the multi-target potential of heparin as a therapeutic option for Alzheimer's disease, the repurposing of this medically important biomolecule has to-date been precluded by its high anticoagulant potential. An alternative source to mammalian-derived glycosaminoglycans are those extracted from marine environments and these have been shown to display an expanded repertoire of sequence-space and heterogeneity compared to their mammalian counterparts. Furthermore, many marine-derived glycosaminoglycans appear to retain favourable bioactivities, whilst lacking the high anticoagulant potential of their mammalian counterparts. Here we describe a sulphated, marine-derived glycosaminoglycan extract from the Atlantic Sea Scallop, Placopecten magellanicus that displays high inhibitory potential against BACE-1 (IC50 = 4.8 μg.mL −1 ) combined with low anticoagulant activity; 25-fold less than that of heparin. This extract possesses a more favourable therapeutic profile compared to pharmaceutical heparin of mammalian provenance and is composed of a mixture of heparan sulphate (HS), with a high content of 6-sulphated N-acetyl glucosamine (64%), and chondroitin sulphate. Graphical abstract: Image 1 Highlights: A GAG extract from the Atlantic Sea Scallop, P. magellanicus, inhibits BACE-1, a key drug-target in Alzheimer's disease. The GAG extract is predominantly HS, containing a high content of UA-GlcNAc(6S), uncommon in mammalian-derived HS. The GAG extract possesses highly attenuated anticoagulant potential compared to mammalian-derived heparin.